KAHATEX BANDUNG REGENCY'S EMPLOYEE SELECTION AND PLACEMENT IMPACT - Warkianto Widjaja; Tini Kartini; Erni Yuningsih; Muhammad Yusuf; Feb Amni Hayati (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to look into the effects of employee placement and selection at PT Kahatex in Bandung Regency. Simple random sampling was used in this study's 699-person population, and it produced a sample of 86 participants. The SPSS version 22 program was used to test the hypothesis in this study, which uses descriptive statistical analysis techniques. A significant value of 0.000 0.05 in the F test results indicates that both the selection and placement variables have an impact on employee performance. The t-test reveals that the selection variable only slightly affects worker performance.